Analysis of Financial Performance Determinants of Companies in the Function of Strategic Management - Vuković, Bojana; Mijić, Kristina; Jakšić, Dejan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Strategic performance management is aimed at the realization of determined goals of the company through efficient and effective management in accordance with the ever-growing requirements of the business environment. This paper aims to investigate the key determinants of company’s financial performance and provides adequate information support for strategic decision making. The sample will include 90 large companies operating in the field of manufacturing in the European market in 2015-2018. years. By applying relevant statistical methods, the paper will be analyzed the impact of current liquidity, the ratio of short-term debt to total assets, total debt to equity, company size, asset tangibility on financial performance measured by return on assets and return on equity. The obtained results aim to define guidelines for improving performance in order to optimize business and ensure the growth, development and competitiveness of European companies. In addition, it should be borne in mind that the process of strategic performance management also requires consideration of non-financial factors such as the level of education and skills of employees, organizational culture and the level of information systems development.